2021
DOI: 10.1016/j.jbo.2020.100330
|View full text |Cite
|
Sign up to set email alerts
|

The HMGB1/RAGE axis induces bone pain associated with colonization of 4T1 mouse breast cancer in bone

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…The p73 protein is known to regulate the genes responsible for metastasis, but the direct association is not always established. For example, HMGB1, a putative p73 target that can regulate p73-mediated transactivation [ 129 , 130 ], is associated with EMT, metastasis, and poor prognosis in breast, lung, and other cancer types [ 55 , 131 , 132 , 133 ].…”
Section: Activation Of Invasion and Metastasismentioning
confidence: 99%
“…The p73 protein is known to regulate the genes responsible for metastasis, but the direct association is not always established. For example, HMGB1, a putative p73 target that can regulate p73-mediated transactivation [ 129 , 130 ], is associated with EMT, metastasis, and poor prognosis in breast, lung, and other cancer types [ 55 , 131 , 132 , 133 ].…”
Section: Activation Of Invasion and Metastasismentioning
confidence: 99%
“…Pain is a common symptom in cancer patients ( Sheng and Zhang, 2020 ). Previous studies have shown that 85% of patients with lung, breast and prostate cancer appear bone metastasis, and about one-third of them was accompanied with bone cancer pain (BCP) symptoms ( Okui et al, 2021 ). Bone cancer pain (BCP) is a unique pain that includes features of nociceptive, neuropathic, and inflammatory pain ( de Clauser et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data showed that CABP is evoked in association with pathological neurogenesis, reprogramming and axonogenesis of SNs in concert with sensitization (a reduction in the threshold and an increase in the magnitude of a response to noxious stimulation) and excitation of SNs by a variety of neurotrophic factors, cytokines and chemokines that are produced in the tumor microenvironment in bone [8] , [10] , [33] . We and others found that cancer progression in bone promotes pathological sprouting and excitability of bone-innervating SNs, thereby eliciting CABP [34] , [35] , [36] , [37] . Thus, CABP is fundamentally a consequence of sensitization and excitation of SNs innervating bone.…”
Section: Pathophysiology Of Cabpmentioning
confidence: 76%
“…We have recently reported that CABP is induced following inoculation of 4T1 mouse breast cancer cells into the bone marrow cavity of tibiae of female BALB/c mice [37] . The 4T1 breast cancer cells aggressively grew with extensive osteolytic lesions in bone.…”
Section: Role Of Sns In Cancer Progression In Bone and Secondary Metastasis From Bonementioning
confidence: 99%
See 1 more Smart Citation